Pengaruh Faktor Sosial dan Ekonomi terhadap Tingkat Literasi Keuangan Mahasiswa - Sari, Salza Nabila; Asriany, Asriany; Riyanti, Riyanti (Jurnal Manajemen Bisnis dan Keuangan, 2025)
This study aims to examine the influence of social and economic factors on students’ financial literacy. The research employed a quantitative approach using a survey design. The sample consisted of 80 students from the Faculty of Economics and Business at Universitas Muhammadiyah Palopo, class of 2022, selected through a simple random sampling technique. Data were collected via an online questionnaire that had been tested for validity and reliability, and then analyzed using multiple linear regression. The findings reveal that students’ financial literacy is significantly influenced by both social and economic factors, whether tested individually (partially) or jointly (simultaneously). The combined contribution of these two factors to the variation in financial literacy levels was recorded at 48,6%. Based on these results, it is recommended that educational institutions enhance students’ social and economic capacities by providing financial training programs, facilitating access to economic information, and fostering a supportive social environment to promote improved financial literacy.